Color vision devices for color vision deficiency patients: A systematic review and meta‐analysis. Issue 5 (22nd September 2022) - Male, Shiva Ram; Shamanna, Bindiganavale R; Bhardwaj, Rishi; Bhagvati, Chakravarthy; Theagarayan, Baskar
Abstract: Background and Aims: There is insufficient evidence to support that using electronic or optical color vision devices improve color perception with current advanced technology. The purpose of this study is to compare and analyze the different color vision devices available for patients with color vision deficiency (CVD) and evaluate whether these devices improved their color perception. Methods: This review included randomized, experimental, comparative studies, as well as narrative reviews, prototype and innovation studies, and translational studies, followed by case‐control and clinical trials with nonsurgical interventions studies, that is, electronic color vision devices, optical devices, and contact lens‐based studies, with standardized inclusion and exclusion criteria. Results: The primary outcome studied was the performance of color vision devices, both objective and subjective. Secondary outcomes included the ease of use and accessibility of color vision devices and technology. The grading of recommendation, assessment, development, and evaluation framework was used to develop a systematic approach for consideration and clinical practice recommendation for CVD devices for color‐deficient populations. We incorporated meta‐analysis reports from a total of n  = 16 studies that met the criteria which consisted of case‐control studies, prototype and innovation studies, comparative studies, pre‐ and post‐clinical trial studies, case studies, and narrative reviews. Proportion and standard errors, as well as correlations, were calculated from the meta‐analysis for various available color vision devices. Conclusion: This review concludes that commercially available color vision devices, such as EnChroma Glasses, Chromagen filters, and EnChroma Cx‐14 do not provide clinically significant evidence that subjective color perception has improved. As a result, recommending these color vision devices to the CVD population may not prove high beneficial/be counterproductive. However, only a few color shades can be perceived differently. This systematic review and analysis will aid future research and development in color vision devices.